An Assessment of Arms Proliferation and Control Mechanisms in Nigeria, 2010-2020 - Eyina, Nkatomba Nkatomba; Kabari, John Baribor, Ph.D (Researchparks Publishing, 2021)
At independence in 1960, the Nigerian State was faced with challenges bordering on national integration and development. Though endowed with abundant human and natural resources, the goal of achieving overall national development through unity was truncated by consistent armed conflicts and criminality that has become part of the Nigerian State. Therefore, this study critically assessed arms proliferation and control in Nigeria from 2010-2020. The historical challenges and solutions of arms proliferation in Nigeria were reviewed and examined. The paper was guided by Radical Structural Conflict and Failed State Theories. The study was anchored on a qualitative method. The data were gathered through secondary sources, which were subjected to content analysis. The study identified porous borders, inefficient monitory mechanisms, saboteurs in the military, and poor working conditions of the security officials as the significant causes of arms proliferation in Nigeria. It was concluded that the accumulation of small arms and their diffusion into the larger society is both casual and symptomatic of the erosion of governance. Therefore, the study recommended, among other things, intensive policing and efficient monitoring mechanisms of the Nigerian borders; identifying the saboteurs in the military and other security agencies; engaging the services/supports of Nigerian citizens; improvement of employment and working conditions of law enforcement agencies would help in curtailing the proliferation of arms in Nigeria.